Exploring indigenous knowledge on medicinal plants used to treat COVID-19 related symptoms - Rankoana, Sejabaledi A. (Technium Social Sciences Journal, 2021)
The purpose of this study was to describe the indigenous plant-derived medicine used to treat symptoms related to four of the most common symptoms of the COVID-19 pandemic. Data presented in this study form part of a medical ethnobotanical study conducted in Limpopo Province, South Africa between 2012 and 2019. The study recorded 89 plant species identified as sources of medicine. Of these plants, 13 species belonging to 9 botanical families were used as sources of medicine to cure influenza, cough, sore throat and fever, while 5 species belonging to 5 botanical families were sources of preventive medicine. The treatment of the four symptoms is accomplished through the administration of oral decoctions, steaming and infusions, while preventive medicine is in the form of infusion, decoction, chew or charm, which is used to prevent susceptibility to infectious diseases such as influenza and cough. Knowledge of these medicines rests with ordinary community members who offer treatment after observations of the symptoms on their family members. The indigenous plant-derived medicines identified in this study may be tested for their safety and efficacy to discover new local, affordable and culture-specific drugs that could be used in the modern phytotherapy for conditions such as COVID-19.